The Experimental Study on Anti-inflammation and Anti-oxidation of Sopungdojeok-tang(Xiaofengdaochi-tang) and Samulsopungsan(Siwuxiaofeng-san) - Hyung-Sik Seo (Korean Pharmacopuncture Institute, 2010)
Objective: This experimental study was performed to investigate the anti-inflammation and anti-oxidant effects of Sopungdojeok-tang(SPDJT) and Samulsopung-san(SMSPS) which were used to treat patient with atopic dermatitis Methods: Anti-inflammation and anti-oxidant effects of SPDJT and SMSPS were measured by the inhibitory ability of Nitric oxide(NO) production and the scavenging for 1,1-diphenyl-2-picrylhydrazyl(DPPH) radical. Results: 1. SPDJT and SMSPS were not showed cell toxicity. 2. In inhibitory effects against NO production, all groups of SPDJT were showed anti-inflammation, but all groups of SMSPS were not showed anti-inflammation. There were statistical significances between 20㎍/㎖ and 4, 10㎍/㎖ in SPDJT groups. 3.In DPPH radical scavenging activity, all groups of SPDJT and all groups of SMSPS were showed anti-oxidant effects. There were statistical significances between 20㎍/㎖ SPDJT group and 4, 10㎍/㎖ SMSPS groups. Conclusion: These results suggest that the SPDJT groups are better than the SMSPS groups in antiinflammation and anti-oxidant effects.